2022
DOI: 10.3390/ijerph19020989
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Characteristics of the Knee Joint during Gait in Obese versus Normal Subjects

Abstract: Knee osteoarthritis (OA) is a growing source of pain and disability. Obesity is the most important avoidable risk factor underlying knee OA. The processes by which obesity impacts osteoarthritis are of tremendous interest to osteoarthritis researchers and physicians, where the joint mechanical load is one of the pathways generally thought to cause or intensify the disease process. In the current work, we developed a hybrid framework that simultaneously incorporates a detailed finite element model of the knee j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The geometry of the tibiofemoral joint was adjusted to align with the dimension reported in the Simtk.org open knee public domain repository [11]. In the model, bones were represented as rigid bodies [19][20][21][22][23] utilizing shell elements (S4R), whereas articular cartilages, ligaments, and menisci were depicted through reduced integration brick elements (C3D8R), as shown in Fig 1 . Details of the knee model were presented in the S1 File and our prior works [24][25][26][27].…”
Section: I) Kinematics-driven Modelmentioning
confidence: 99%
“…The geometry of the tibiofemoral joint was adjusted to align with the dimension reported in the Simtk.org open knee public domain repository [11]. In the model, bones were represented as rigid bodies [19][20][21][22][23] utilizing shell elements (S4R), whereas articular cartilages, ligaments, and menisci were depicted through reduced integration brick elements (C3D8R), as shown in Fig 1 . Details of the knee model were presented in the S1 File and our prior works [24][25][26][27].…”
Section: I) Kinematics-driven Modelmentioning
confidence: 99%
“…95 Fadi et al developed a musculoskeletal model to study lower limb muscle strength and knee joint stress in average-weight and obese people, finding that obese people had significantly greater muscle strength, greater relative motion of the medial compartment in the knee, and relatively more significant cartilage stress. 96 Arjmand et al proposed an FEM to accurately quantify the changes in mechanical parameters in normal populations and patients with OA, 97 finding that the bone stress in the proximal tibia was higher in patients with OA, which might be necessary for understanding the pathogenesis of knee OA. 97 Peter et al explored the influence of the morphology of the distal femoral epiphysis surface on the epiphysis biomechanics through finite element modeling and found that a complex-shaped articular surface could reduce the stress on the epiphysis during knee flexion.…”
Section: Osteoarthritismentioning
confidence: 99%
“…Fadi et al . developed a musculoskeletal model to study lower limb muscle strength and knee joint stress in average‐weight and obese people, finding that obese people had significantly greater muscle strength, greater relative motion of the medial compartment in the knee, and relatively more significant cartilage stress 96 …”
Section: Application and Characteristicsmentioning
confidence: 99%
“…Obesity is also a risk factor for canine OA, with a recent systematic review for canine OA risk factors concluding that overweight dogs were significantly more likely to develop stifle OA secondary to cranial cruciate ligament disease (Anderson et al 2020). Obesity leads to increased compressive forces on load-bearing joints and alters joint kinematics during gait (Brady et al 2013, Al Khatib et al 2022. A biochemical as well as biomechanical link between obesity and OA is likely, as adipose tissue is a metabolically active endocrine organ synthesising and secreting hormones such as adipokines (Coelho et al 2013).…”
Section: Weight Managementmentioning
confidence: 99%
“…2013, Al Khatib et al . 2022). A biochemical as well as biomechanical link between obesity and OA is likely, as adipose tissue is a metabolically active endocrine organ synthesising and secreting hormones such as adipokines (Coelho et al .…”
Section: Weight Managementmentioning
confidence: 99%